(untitled) (Vietnam Journal of Community Medicine, 2021)
A cross-sectional study on 322 students studying at Hanoi Medical University on the impact of the COVID-19 pandemic on student learning outcomes. The result show that the majority of students switch to learning via Zoom, Microsoft Team, Skype, GoogleMeeting applications (accounting for 98.5%). Most of the students have the best equipment and conditions for trực tuyến learning at home: desks (96.58%); computers (88.51%); software and curriculum (95.65%); office furniture (97.20%); good internet connection (80.12%). It is necessary to develop appropriate learning methods and forms for Hanoi medical students, especially clinical practice content.